The Inherent Trajectory of Lên đồng: Its Ambiguity and the Debate - Nguyen Thi Hien, (Tạp chí Khoa học Xã hội và Nhân văn (VNU Journal of Social Sciences and Humanities), 2025)
Lên đồng is a practice of the Việt beliefs in Mother Goddesses of Three and Four Realms or so-called Mother Goddess Religion.  It is a possession ritual in which the spirit mediums incarnate a number of spirits of the pantheon. In the past, before the Renovation (1986), lên đồng used to be seen as “a superstition” and was banned from practicing. However, the destined mediums were still initiated and performed the ritual. Today, lên đồng has been reevaluated and regarded as an intangible cultural heritage of the Vietnamese people.  The development of the ritual in contemporary society with the different performing style and performance on stage makes scholars, cultural managers and the spirit mediums themselves preoccupy and debate how to direct lên đồng, as an intangible cultural heritage into its inherent trajectory.  What is the inherent trajectory? Its ambiguity and the debate on the issues of today’s lên đồng such as the Lên đồng performance on lên đồng performance on stage folklorization, the high emphasis on the artistic aspects of lên đồng, its discrepancy, standardized rituals, and the devotion of the spirit mediums are the concerns of my paper.  With my research experience and having witnessed the development of lên đồng since the 2000s, my recent fieldwork on lên đồng rituals in Vietnam and abroad, in this paper, I will examine the issues of today’s lên đồng and the debates among researchers, cultural managers, and the spirit mediums on the inherent trajectory of lên đồng.Received 15th January 2018; Revised 31st July 2018; Accepted 20th October 2018